(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
A business cannot flourish unless and until it takes care of its environment, its society and its people. It has an obligation to deliver goods and services in such a way that it does not harm the environment or its stakeholders and thus has customer and society’s welfare as its goal and not mere maximisation of profits. People will lose confidence in an organisation which is harming the country’s resources or not working for the best interests of its stakeholders as was identified by (Norwal & Sharma, 2006) who discussed that crisis is the real test of capabilities and socially responsible companies are perceived differently by people. Thus, companies who are serving the society well, will be able to persist in the long run while the others may even end up losing their competitive advantage. This concept is no less important for financial firms. Financial companies like Banks and Non-Banking Financial Companies (NBFCs) play an important role in meeting the funding requirements of other firms and acts as a mediator of funds from the one who have funds to the ones who need funds. A financial firm engaged in serving the society will have a positive image and will be able to retain its customers even in the times of financial crisis. The purpose of study is to shed light on the Corporate Social Responsibility (CSR) practices discharged by most profitable Public Sector Banks, Private Sector Banks and NBFCs in India and their comparison as to their contribution towards CSR activities. It was found that Private Sector Banks and NBFCs are more active as to its contribution towards CSR and it corresponds to its better performance.